2011
DOI: 10.1016/j.molcel.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic piRNA Ping-Pong Requires Qin, a Protein with Both E3 Ligase and Tudor Domains

Abstract: Summary piRNAs guide PIWI proteins to silence transposons in animal germ cells. Reciprocal cycles of piRNA-directed RNA cleavage—catalyzed by the PIWI proteins Aubergine (Aub) and Argonaute3 (Ago3) in Drosophila melanogaster—expand the population of antisense piRNAs in response to transposon expression, a process called the Ping-Pong cycle. Heterotypic Ping-Pong between Aub and Ago3 ensures that antisense piRNAs predominate. We show that qin, a piRNA pathway gene whose protein product contains both E3 ligase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 58 publications
7
139
0
Order By: Relevance
“…Transposon mobilization and DNA damage are common to all piRNA pathway mutants, and could contribute to the splicing defects. We therefore analyzed cluster splicing in ovaries mutant for qin , which disrupt a component of the cytoplasmic nuage required for piRNA amplification and transposon silencing (Zhang et al, 2011). In contrast mutations in rhi, cuff and uap56 , the qin mutant combination did not increase spliced transcripts from the sox102F locus (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transposon mobilization and DNA damage are common to all piRNA pathway mutants, and could contribute to the splicing defects. We therefore analyzed cluster splicing in ovaries mutant for qin , which disrupt a component of the cytoplasmic nuage required for piRNA amplification and transposon silencing (Zhang et al, 2011). In contrast mutations in rhi, cuff and uap56 , the qin mutant combination did not increase spliced transcripts from the sox102F locus (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…RNA isolation, small RNA library construction and sequencing data analysis, immunoblotting, immunostaining and quantitative RT-PCR were performed as described (Zhang et al, 2011). Figures were generated using Excel (Microsoft, Redmond, WA, USA), IgorPro (WaveMetrics, Lake Oswego, OR, USA), Adobe Photoshop and Illustrator (Adobe systems, San Jose CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to Aub, Ago3, and Tudor, recent studies have shown that many of the ping-pong cycle components localize to the nuage, such as the RNA helicase Armi, the DEAD-box helicase Vasa (Vas), and the HMG protein Maelstrom (Mael), as well as the TDRD proteins Spn-E, Kumo, Krimp, Vret, and Tej [40,41,6770]. Their nuage localization suggests that the nuage is the cytoplasmic site where the ping-pong cycle takes place.…”
Section: Piwis Tudors and Other Proteins In Pirna Biogenesismentioning
confidence: 99%
“…The authors propose that Vasa, a conserved DEAD box RNA-helicase, promotes transfer of the target RNAs cleaved by Siwi (an Aubergine ortholog) to Ago3 for the secondary biogenesis (Xiol et al, 2014). Several proteins including Tdrd9/Spindle-E and RNF17/Kumo have been identified as factors involved in the secondary biogenesis (Anand and Kai, 2012; Malone et al, 2009; Shoji et al, 2009; Zhang et al, 2011). .…”
Section: Secondary Pirna Biogenesis Pathway and Transposon Suppressionmentioning
confidence: 99%